Authors Collaboration in Digital Literacy From 1997 to 2013 : a bibliometric study - Mathar, Taufiq (Jurnal Ilmu Perpustakaan & Informasi KHIZANAH AL-HIKMAH, 2014)
The study aims to identify the degree of author collaboration among scholars in digital literacy articles published from 1997-2013. The 661 digital literacy articles were gathered and indexed by Web of Science. The study found that the degree of author collaboration was 0.62 or 62%, indicating that more than a half of 661 articles were multi-authored papers. In addition, America Continents have proportionally contributed in discussing about digital literacy topic. It was then followed by European countries, Australia/Oceania, Asia, and Africa respectively. The study also figured out that Eszter Hargittai was the most prolific author who has published 8 articles in different journals on this particular topic.